The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.9734/indj/2021/v15i130144
|View full text |Cite
|
Sign up to set email alerts
|

Stigma Linked to COVID-19

Abstract: When it is safe to do so, medical professionals should not delay the treatment of patients who present with respiratory difficulties. Stigmatization of such patients can result in the unnecessary deferral of emergency therapy; this may lead to fatalities that could have been avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
(27 reference statements)
0
6
0
Order By: Relevance
“… Phelan et al (2008) consider that stigmatization is configured as a mechanism of exploitation or domination, social control, or disease avoidance. Therefore, the fear of infection by coronavirus disease (COVID-19) explains the discrimination related to the pandemic ( Cassiani-Miranda et al, 2020 ), the negative attitude towards people of Asian origin due to the supposed origin of the virus ( Trammell et al, 2021 ; Wen et al, 2020 ) and towards symptomatic people suspected of or diagnosed with COVID-19 ( Nuckchady, 2021 ). In the same way, the fear of COVID-19 promoted violent actions towards health workers due to the employment relationship with the disease ( Chanpa et al, 2020 ; Miconi et al, 2021 ) and towards people who recovered from COVID-19 due to infection ( Singh & Subedi, 2020 ).…”
mentioning
confidence: 99%
“… Phelan et al (2008) consider that stigmatization is configured as a mechanism of exploitation or domination, social control, or disease avoidance. Therefore, the fear of infection by coronavirus disease (COVID-19) explains the discrimination related to the pandemic ( Cassiani-Miranda et al, 2020 ), the negative attitude towards people of Asian origin due to the supposed origin of the virus ( Trammell et al, 2021 ; Wen et al, 2020 ) and towards symptomatic people suspected of or diagnosed with COVID-19 ( Nuckchady, 2021 ). In the same way, the fear of COVID-19 promoted violent actions towards health workers due to the employment relationship with the disease ( Chanpa et al, 2020 ; Miconi et al, 2021 ) and towards people who recovered from COVID-19 due to infection ( Singh & Subedi, 2020 ).…”
mentioning
confidence: 99%
“…The stigma generated by COVID-19 is usually a source of shame, anxiety, and potentially social rejection felt directly by the infected, stigmatized person (or the person considered by others as a possible agent of infection) but also by those close to them (family, friends, health professionals, and communities considered to be more conducive to the existence and transmission of the virus, among others) [15,[26][27][28]. Stigma is almost always regarded for its potentially negative characteristics of social rejection and the various consequences involved, and the same has happened with its association with COVID-19 [11,[29][30][31][32][33][34][35][36][37][38][39][40][41], which may even reinforce pre-existing stereotypes, difficulties, and negative images [33,42]. According to Joshi and Swarnakar [36] (p. 3), "All these cases of infectious-disease stigma rely on a binary between the 'normal' and the 'other' in the form of a culturally defined negative attribute or stigma to pass blame through social positions of power and control".…”
Section: Covid-19 and The Processes Of Stigmatizationmentioning
confidence: 99%
“…The sick, the old, the contaminated, and those with bodily marks of physical decay tend to be excluded or ignored [45]. Nuckchady [34] (p. 32) presents a categorization of infected individuals, and thus potential victims of stigmatization, into the following four groups: "[...] stigma of people who are perceived to be carriers of the disease but who most likely are not infected, stigma of people who are actually infected, stigma of people who were infected but who have recovered and are no longer contagious and stigma towards people who care for the ill".…”
Section: Covid-19 and The Processes Of Stigmatizationmentioning
confidence: 99%
“…However, during the COVID-19 pandemic, HCWs are also found to have developed social stigma towards COVID-19 patients (Aacharya & Shah, 2020;Grover et al, 2020). Such stigma can disrupt doctor-patient relationships leading to a poor diagnosis, affecting prevention measures and management of illnesses and therefore could disturb the mental health of the patients (Chopra & Arora, 2020;Nuckchady, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that some HCWs and some hospitals have denied admission and treatment for COVID-19 patients (Nuckchady, 2021), indicating fear and stigma among HCWs and those working within healthcare facilities towards COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%